2014
DOI: 10.1177/0961000614532677
|View full text |Cite
|
Sign up to set email alerts
|

Comparing digital libraries in the web and mobile contexts from the perspective of the digital divide

Abstract: Building on concepts of the digital divide, this study explores and compares users’ perceptions of web digital libraries and mobile digital libraries in terms of ease of use and usefulness. Data collected from 306 university library users were analyzed. Two figures were used to present the exact nature of users’ perceptions of ease of use and usefulness in terms of data distribution. These figures were supplemented by the paired samples t test which presents the exact mean difference between web digital librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
0
19
0
2
Order By: Relevance
“…Various models such as EECM (Joo & Choi, 2015) and UTAUT (Venkatesh, Morris, Davis, & Davis, 2003) are presented in the literature to investigate the intention of people regarding technology adoption. Among these models, TAM has been extensively used for recognizing the factors affecting the acceptance of technology in a variety of contexts like USA, KSA, Korea, China, (Rafique et al, 2018) (Zha et al, 2015) (Yoon, 2016) and in various domains like m-shopping (Hubert et al, 2017), e-learning (Jeong, 2011), online libraries (Zhao et al, 2015), digital libraries (Zha et al, 2015), and MLA (Joo & Choi, 2015) (Aharony, 2014). TAM was extended from the theory of reasoned action (TRA), which says, the behaviour of an individual is determined by his/her behavioural intention (BI) whereas, BI is determined by subjective norms and attitude (Ajzen & Fishbein, 1977).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models such as EECM (Joo & Choi, 2015) and UTAUT (Venkatesh, Morris, Davis, & Davis, 2003) are presented in the literature to investigate the intention of people regarding technology adoption. Among these models, TAM has been extensively used for recognizing the factors affecting the acceptance of technology in a variety of contexts like USA, KSA, Korea, China, (Rafique et al, 2018) (Zha et al, 2015) (Yoon, 2016) and in various domains like m-shopping (Hubert et al, 2017), e-learning (Jeong, 2011), online libraries (Zhao et al, 2015), digital libraries (Zha et al, 2015), and MLA (Joo & Choi, 2015) (Aharony, 2014). TAM was extended from the theory of reasoned action (TRA), which says, the behaviour of an individual is determined by his/her behavioural intention (BI) whereas, BI is determined by subjective norms and attitude (Ajzen & Fishbein, 1977).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers had widely used TAM to investigate the behavior of a users toward using new information systems and technology in a library setting (online library resource, digital library and MLA (Rafique et al, 2018) (Zha et al, 2015) (Yoon, 2016) (Zhao et al, 2015) (Aharony, 2014) (Miller & Khera, 2010). The research conducted in developing countries Kenya and Peru identified the factors influencing the usage of digital libraries by applying TAM (Miller & Khera, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TAM is widely used to examine the process of individuals’ acceptance of technology. The TAM, arising from the theory of reasoned action ( Madden et al, 1992 ), is developed by Davis (1989) , and then extensively used in the technology acceptance field to explain technology use behavior ( Zha et al, 2015 ; Yoon, 2016 ; Rafique et al, 2018 ; Teo et al, 2018 ). The TAM contains core components, i.e., use motivation, including perceived ease of use, perceived usefulness, and outcomes including behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teknoloji kabul modeli, literatürde bireylerin çeşitli açılardan teknoloji kabulünü etkileyen faktörleri tanımlamak için kullanılan en geniş çaplı model olarak kabul edilmektedir (Rafique, Almagrabi, Shamim ve Bashir, 2020). Teknoloji kabul modeli ile ilgili geçişte yapılan çalışmalar incelendiğinde; bu modelin yaygın olarak e-öğrenme, online kütüphane ve dijital kütüphane uygulamalarında (Miller ve Khera, 2010;Jeong, 2011;Aharony, 2014;Joo ve Choi, 2015;Zha, Zhang ve Yan, 2015;Zhao, Deng ve Zhou, 2015;Yoon, 2016;Rafique, vd., 2018), mobil alışveriş (Wu ve Wang, 2005;Hubert, Blut, Brock, Backhaus ve Eberhardt, 2017) ve mobil ödeme (Liébana-Cabanillas, Sánchez-Fernández ve Muñoz-Leiva, 2014;Shin ve Lee, 2014;Koenig-Lewis, Marquet, Palmer ve Zhao, 2015;Pham ve Ho, 2015;Slade, Williams, Dwivedi ve Piercy, 2015;Yan ve Pan, 2015;Oliveira, vd., 2016;Schmidthuber, vd., 2020) alanlarında kullanıldığı görülmektedir.…”
Section: Literatür Teknoloji Kabul Modeliunclassified
“…Khera, 2010;Jeong, 2011;Aharony, 2014;Joo ve Choi, 2015;Zha, Zhang ve Yan, 2015;Zhao, Deng ve Zhou, 2015;Yoon, 2016; Rafique, vd., 2018), mobil alışveriş(Wu ve Wang, 2005; Hubert, Blut, Brock, Backhaus ve Eberhardt, 2017) ve mobil ödeme (Liébana-Cabanillas, Sánchez-Fernández ve Muñoz-Leiva, 2014; Shin ve Lee, 2014; Koenig-Lewis, Marquet, Palmer vePham ve Ho, 2015;Slade, Williams, Dwivedi ve Piercy, 2015;Yan ve Pan, 2015; …”
mentioning
confidence: 99%